Nkanelo wa nxopaxopo wa mavito yo khovolela eka Xitsonga - Mabasa, S. M. (My University, 2013)
Refer to the document
The Analysis of the origins of the humorous nicknames in Xitsonga
Thesis (M.A. (African Languages)) --University of Limpopo, 2013
Keywords: Nicknames; Tsonga people; Tsonga (African people); Nicknames -- South Africa; Etymology